The impacts of the EU ETS on efficiency: An empirical analyses for German manufacturing firms - Andreas Löschel; Benjamin Johannes Lutz; Shunsuke Managi (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We investigate the effect of the European Union Emissions Trading System (EU ETS) on the economic performance of manufacturing firms in Germany. Our difference-in-differences framework relies on several parametric conditioning strategies and nearest neighbor matching. As a measure of economic performance, we use the firm specific distance to the stochastic production frontier recovered from official German production census data. None of our identification strategies provide evidence for a statistically significant negative effect of emissions trading on economic performance. On the contrary, the results of the nearest neighbor matching suggest that the EU ETS rather had a positive impact on the economic performance of the regulated firms, especially during the first compliance period. A subsample analysis confirms that EU ETS increased the efficiency of treated firms in at least some two-digit industries.
urn:nbn:de:bsz:180-madoc-417995
Keywords: Q52; D22; Q38; Q48; 330; Control of Externalities; Emissions Trading; Economic Performance; Manufacturing; Difference-in-Differences; Nearest Neighbor Matching; Stochastic Production Frontier